Proceedings of the 2014 Conference on Interactive Entertainment 2014
DOI: 10.1145/2677758.2677764
|View full text |Cite
|
Sign up to set email alerts
|

Extending Building Information Models into Game Engines

Abstract: The use of detailed building plans and models is common in the construction management domain. Also there is increasing interest in the reuse of such models to realize 3D interactive virtual environments to aid model refinement and for use as training environments, for example virtual site visits. Unfortunately, the development of interactive virtual environments is both time consuming and technically difficult. One successful approach is the reuse of gaming technology to provide the underlying virtual environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 17 publications
0
46
0
Order By: Relevance
“…In the built environment, these may either be interiors or outdoor environments (Fritsch and Kada, ). In this area of interest, several methods have been developed to convert geographical information system (GIS) data (Virtanen et al., ) and building models (Bille et al., ) into formats compatible with game engines. This allows creation of a virtual environment for existing data sources.…”
Section: Introductionmentioning
confidence: 99%
“…In the built environment, these may either be interiors or outdoor environments (Fritsch and Kada, ). In this area of interest, several methods have been developed to convert geographical information system (GIS) data (Virtanen et al., ) and building models (Bille et al., ) into formats compatible with game engines. This allows creation of a virtual environment for existing data sources.…”
Section: Introductionmentioning
confidence: 99%
“…Reapplication of textures, heaviness of the models generated in BIM authoring tools in the rendering and VE navigation, manually re-entering information to gaming engines, and interoperability between the BIM authoring tools and the gaming engines are highly referred challenges in the literature (e.g. Nopachinda, Ergan 2016;Shen et al 2007Shen et al , 2012Dalton, Parfitt 2013;Figueres-Munoz, Merschbrock 2015;Bille et al 2014).…”
Section: Challenges In Converting Bims To Ves For Aec/fm Usementioning
confidence: 99%
“…Figueres-Munoz et al (Shiratuddin & Thabet, 2011) indicated that integration of BIM and gaming technology has the potential for combinatorial innovation. A number of previous studies have proposed methods for integrating game engine, BIM, and VR experience for various purposes, e.g., design review (e.g., (Shiratuddin & Thabet, 2011;Wu, 2015)), construction management (e.g., (Bille et al, 2014)), education (e.g., (Wu, 2015;Goedert et al, 2011)), energy conservation (e.g., (Niu et al, 2015;Jalaei & Jrade, 2014;Brewer et al, 2013)), real-time architectural visualization (e.g., (Yan et al, 2011)), and design feedback (e.g., (Hosokawa et al, 2016;Fukuda et al, 2015;Bahar et al, 2013;Motamedi et al, 2016)). …”
Section: Literature Reviewmentioning
confidence: 99%
“…However, such tools can only provide static outputs with no interaction between the users and the environment e.g., (Bille et al, 2014;Kumar et al, 2014), and are inadequate for dynamically updating or changing design parameters (Kensek & Noble, 2013) and providing simultaneous energy feedback when comparing multiple design scenarios. Moreover, when using traditional tools, designers are unable to directly experience some lighting phenomena that may affect the visual perception of the occupants, e.g., brightness, darkness, glare, or insufficient illumination.…”
Section: Introductionmentioning
confidence: 99%